Comparison of Macular Choroidal Thickness and Volume between Pseudoexfoliative Glaucoma and Pseudoexfoliative Syndrome - Fan Li; Lihua Ma; Yulei Geng; Xiaowei Yan; Hengli Zhang; Guangxian Tang; Qingli Shang (Journal of Ophthalmology)
Purpose. To evaluate the difference in macular choroidal thickness and volume between patients with pseudoexfoliative glaucoma (PXG), patients with pseudoexfoliative syndrome (PEX), and normal controls. Methods. This case-control study included 49 PXG patients (group A), 33 PEX patients (group B), and 42 sex-, age-, and axial length-matched healthy volunteer eyes (group C). The macular choroidal thickness and volume of all subjects studied were measured by enhanced depth imaging optical coherence tomography. Results. The average macular (AM) choroidal thickness was 170.79 ± 50.18 μm, 184.65 ± 57.54 μm, and 206.46 ± 48.90 μm, and the average volume was 0.52 ± 0.15 μm3, 0.56 ± 0.17 μm3, and 0.63 ± 0.15 μm3 in groups A, B, and C, respectively. The macular choroidal thickness, the volumes of various macular regions, and the average choroidal thickness and volume in group A were lower than those in group C (all P<0.05). There were no significant differences in the macular choroidal thickness, volumes of various macular regions, or average choroidal thickness or volume between group A and B (all P>0.05). The macular choroidal thickness and volume of the TIM and SOM in group B were lower than those in group C (P<0.05). There was no association between the macular choroidal thickness of various macular regions and visual field mean defect (MD) in group A (all P>0.05). Conclusion. The macular choroidal thickness in patients with PXG or PEX (TIM and SOM) is thinner than that in normal subjects. The macular choroidal thickness in patients with PXG is not significantly different from that in patients with PEX. The role of macular choroidal thickness changes in the glaucomatous damage of patients with PXG is still unclear.